A reader in medical anthropology : theoretical trajectories, emergent realities - Good, Byron J. (Chichester, West Sussex, U. K. ; Malden, Massachusetts : Wiley-Blackwell, 2010)
Presents a key collection of both classic and new agenda-setting articles in this central area of anthropology ? Provides analytic and historical contextual introductions by leading figures in medical anthropology, medical sociology, science studies, social theory and general anthropology
1. Antecedents -- 2. Illness and narrative, body and experience -- 3. Governmentalities and biological citizenship -- 4. The biotechnical embrace -- 5. Biosciences, biotechnologies -- 6. Global health, global medicine -- 7. Postcolonial disorders
Includes bibliographical references and index
Keywords: Medical anthropology; Traditional medicine